DNA Nanostructures in the Fight Against Infectious Diseases. Issue 3 (5th March 2021) - Smith, David M.; Keller, Adrian
Abstract : DNA Nanostructures The COVID‐19 pandemic has reminded us once more that humanity is constantly threatened by epidemic outbreaks of infectious diseases. In article number 2000049, David M. Smith and Adrian Keller provide a brief overview of recently developed strategies in infectious disease diagnostics, treatment, and prevention based on DNA nanotechnology.